STUDY OF THE IMPACT OF THREE SPECIES OF ATRIPLEX (ATRIPLEX HALIMUS, ATRIPLEX NUMMULARIA AND ATRIPLEX CANESCENS) ON THE SOIL PHYSICO-CHEMICAL PARAMETERS IN THE STEPPE ZONE; CASE OF THE SOUTH WEST OF ALGERIA - Yahiaoui, Fatima Zohra; Labani, Abderrahmane; Terras, Mohamed; Anteur, Djamel; Adda-Hanifi, Nadia Nora; Kerache, Ghaouti; Hadouche, Moulay Idriss (European Scientific Journal, ESJ, 2014)
The introduction on large areas of the genus Atriplex, in the Algerian steppe zone characterized by a fragile soil with an intense human and climate pressures, requires a study of its impact on the soil physico-chemical characteristics. The introduction of three species of Atriplex: a local specie Atriplex halimus, a second is Atriplex canescens originally from America and the third Atriplex nummularia from Australia. In each of these three species planting perimeter planted before 7 years a collect of the soil samples was conducted in the spring. The comparison between the soils results of the three species reveals the impact of Atriplex on some soil characteristics. The specie that improves the soil and does not disturb its physico-chemical characteristics is the local specie Atriplex halimus.